Improving Cognition Through APE (Educational Game Tools) - Ulfadhilah, Khairunnisa; Salsabila Dwi Nurkhafifah (UIN Mataram, 2024)
This research was conducted to identify how to improve cognition with the use of educational game tools in PAUD Darussalam Cirebon. The research method of the treatment group was qualitative using observation to PAUD Darussalam Cirebon and then interviews with the principal, teachers of class A and class B and their parents as representatives of class A and class B. The research consisted of children in PAUD Darussalam Cirebon. The treatment group was given access to a variety of educational game tools for one month, while the control group was given no additional intervention. The research method was carried out qualitatively and then observation, interviews and documentation were carried out at PAUD Darussalam Cirebon. The results of the study at PAUD Darussalam Cirebon show that children involved in the use of APE are highly recommended to become school facilities because it is very good for children's growth and development from an early age so that it will be optimal. In addition, APE is a learning medium when in class by learning while playing so that a fun classroom atmosphere is very appropriate for educators at PAUD Darussalam Cirebon. Educators should consider integrating educational play tools into their curriculum as a means to improve children's cognitive abilities. In addition, parents can also take advantage of educational play tools at home to help their children's cognitive development.